2023
DOI: 10.7717/peerj.14714
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptome analysis of Armillaria gallica 012m in response to ethephon treatment

Abstract: Background Gastrodia elata, known as a rootless, leafless, achlorophyllous and fully mycoheterotrophic orchid, needs to establish symbionts with particular Armillaria species to acquire nutrition and energy. Previous research findings had approved that ethylene (ET) played an important role in plant-fungi interaction and some receptors of ET had been discovered in microorganisms. However, the molecular mechanisms underlying the role of ET in the interaction between G. elata and Armillaria speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…Organisms possess the ability to modulate the expression of a substantial number of genes as a means to adapt to various environmental conditions. 56,57 In another study analyzing the interaction between the biocontrol rhizobacterium Lysobacter capsici AZ78 and the soilborne phytopathogenic oomycete Phytophthora infestans, findings were made that a certain number of important pathways involved in pathogen attack were significantly upregulated in Lysobacter capsici, and several primary metabolic pathways were down-regulated in P. infestans. 58 The current study found that very less reads of the RNA-Seq for the interacting samples were mapped into the genome of P. capsici, suggesting that the vitality of P. capsici was considerably lower when subjected to hyperparasitism by T. harzianum compared to P. infestans interacting with L. capsici.…”
Section: Discussionmentioning
confidence: 99%
“…Organisms possess the ability to modulate the expression of a substantial number of genes as a means to adapt to various environmental conditions. 56,57 In another study analyzing the interaction between the biocontrol rhizobacterium Lysobacter capsici AZ78 and the soilborne phytopathogenic oomycete Phytophthora infestans, findings were made that a certain number of important pathways involved in pathogen attack were significantly upregulated in Lysobacter capsici, and several primary metabolic pathways were down-regulated in P. infestans. 58 The current study found that very less reads of the RNA-Seq for the interacting samples were mapped into the genome of P. capsici, suggesting that the vitality of P. capsici was considerably lower when subjected to hyperparasitism by T. harzianum compared to P. infestans interacting with L. capsici.…”
Section: Discussionmentioning
confidence: 99%